2016
DOI: 10.4103/2045-9912.196904
|View full text |Cite
|
Sign up to set email alerts
|

Molecular hydrogen: a therapeutic antioxidant and beyond

Abstract: Molecular hydrogen (H2) medicine research has flourished since a landmark publication in Nature Medicine that revealed the antioxidant and cytoprotective effects of hydrogen gas in a focal stroke model. Emerging evidence has consistently demonstrated that molecular hydrogen is a promising therapeutic option for a variety of diseases and the underlying comprehensive mechanisms is beyond pure hydroxyl radicals scavenging. The non-toxicity at high concentrations and rapid cellular diffusion features of molecular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
44
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(47 citation statements)
references
References 39 publications
1
44
0
2
Order By: Relevance
“…[6] H 2 is nontoxic even at high concentrations. [7] Theeffectiveness of H 2 gas against several inflammatory disorders has been demonstrated in animal models following the direct inhalation of H 2 gas,the oral uptake of H 2 water, or the intravenous injection of H 2 saline. [8] However,its bioavailability in body fluids and at inflammatory sites in these methods is typically poor, because the solubility of H 2 in aqueous solutions is very low (ca.…”
mentioning
confidence: 99%
“…[6] H 2 is nontoxic even at high concentrations. [7] Theeffectiveness of H 2 gas against several inflammatory disorders has been demonstrated in animal models following the direct inhalation of H 2 gas,the oral uptake of H 2 water, or the intravenous injection of H 2 saline. [8] However,its bioavailability in body fluids and at inflammatory sites in these methods is typically poor, because the solubility of H 2 in aqueous solutions is very low (ca.…”
mentioning
confidence: 99%
“…More than 30 years later, an important study confirmed the beneficial effects of hydrogen on brain injury by reducing cytotoxic ROS and protecting tissue from oxidative damage [28]. Hydrogen treatments, including inhalation of hydrogen gas and Hydrogen-Rich saline administration, have been tested in many animal models and clinical trials [11, 30, 31]. In general, hydrogen has been described effective in treating a variety range of diseases such as post-cardiac syndrome, Parkinson’s disease, acute cerebral ischemia, metabolic syndrome, rheumatoid arthritis, hemodylisis and postpsoriasis [11, 31, 32].…”
Section: Discussionmentioning
confidence: 99%
“…Hydrogen treatments, including inhalation of hydrogen gas and Hydrogen-Rich saline administration, have been tested in many animal models and clinical trials [11, 30, 31]. In general, hydrogen has been described effective in treating a variety range of diseases such as post-cardiac syndrome, Parkinson’s disease, acute cerebral ischemia, metabolic syndrome, rheumatoid arthritis, hemodylisis and postpsoriasis [11, 31, 32]. For pancreas disease, previous studies suggested hydrogen was protective in experimental acute pancreatitis by ameliorating oxidative stress [17, 33].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Molecular hydrogen (H 2 ) has been reported to have antioxidant-like effects by effectively protecting cells against oxidative stress [1]. Additional research has demonstrated that H 2 exhibits a wide breadth of functions including anti-inflammatory, anti-allergy, anti-apoptosis, and anti-metabolic disorders [2]. In addition to the beneficial roles of H 2 reported in animals, more than 30 studies have reported that it also has an important regulatory effect on the physiological function of plants.…”
Section: Introductionmentioning
confidence: 99%